Mental health service satisfaction among adults with mental illness attending a psychiatric outpatient clinic: a cross-sectional study - Wondale Getinet Alemu; Wondale Getinet Alemu; Lillian Mwanri; Clemence Due; Telake Azale; Anna Ziersch (Frontiers in Public Health)
BackgroundPatient satisfaction with services is both a direct and indirect indicator of healthcare quality. It influences healthcare outcomes, patient retention, and the likelihood of medical malpractice claims. However, there is limited evidence on patient satisfaction with mental health services in Africa. Therefore, we aimed to assess mental health service satisfaction and its determinants in adult patients with mental illness in an outpatient clinic in Northwest Ethiopia.MethodsA hospital-based cross-sectional study was conducted from October to March 2023. Participants were selected using systematic random sampling with a sample interval of three, resulting in a total sample size of 638 invited to participate. Service satisfaction was measured using the interviewer-administered Client Satisfaction Questionnaire-8 (CSQ-8). Data entry, coding, and analysis were performed using SPSS-28. To examine the association of sociodemographic, clinical, social support, and substance use factors, bivariate and multivariate logistic regression analyses were applied. Statistical significance was declared at a p-value of <0.05 and 95% CI.ResultsThe rate of low mental health service satisfaction among people with mental illness in this study was 24.7%. According to our multivariate logistic regression analysis, people with urban residence 1.77 (1.15, 2.72), poor self-reported health 3.62(1.97, 6.67), having episodic illness ≥2/yr. 0.48 (0.32, 0.74), having relapse 1.75 (1.12, 2.73), and poor drug adherence 2.28 (1.20, 4.35) were more likely to have low mental health service satisfaction than their counterparts.Conclusions and recommendationOne-quarter of patients with mental illness in the outpatient clinic reported low satisfaction with mental health services. Factors associated with lower satisfaction included urban residency, episodic illness, relapse, poor self-reported health, and poor drug adherence. To enhance patient satisfaction, the clinic should prioritize targeted support for patients facing these challenges.